2020
DOI: 10.1186/s12882-020-01962-y
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the multi-pronged approach in the diagnosis of Alport syndrome for 22 children in Northeast China

Abstract: Background Alport syndrome (AS) is a kind of progressive hereditary nephritis induced by mutations of different genes that encode collagen IV. The affected individuals usually develop hematuria during childhood, accompanying with gradual deterioration of renal functions. In this study, the multi-pronged approach was employed to improve the diagnosis of AS. Methods Twenty-two children were diagnosed and treated at the Department of Pediatric Nephrology of Jilin Universit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…A review of all reported digenic COL4A5 variants in 16 men with a median age of 16 years (5–55) found that the COL4A5 change was severe in five (31%) and that the additional variant was severe in only two (13%) (16,21,3032) (Table 1). Digenic disease was associated with proteinuria in 12 (12 of 13; 92%) and kidney failure in five (five of 15; 33%), which developed at a median age of 27 (range, 23–47), as well as hearing loss (six of ten; 60%) and ocular abnormalities (three of six; 50%).…”
Section: Pathogenic Variants In Col4a5 Plus Col4a3 or Col4a4 In Men O...mentioning
confidence: 99%
“…A review of all reported digenic COL4A5 variants in 16 men with a median age of 16 years (5–55) found that the COL4A5 change was severe in five (31%) and that the additional variant was severe in only two (13%) (16,21,3032) (Table 1). Digenic disease was associated with proteinuria in 12 (12 of 13; 92%) and kidney failure in five (five of 15; 33%), which developed at a median age of 27 (range, 23–47), as well as hearing loss (six of ten; 60%) and ocular abnormalities (three of six; 50%).…”
Section: Pathogenic Variants In Col4a5 Plus Col4a3 or Col4a4 In Men O...mentioning
confidence: 99%
“…In the present case, a genetic analysis was performed to investigate the origin of the vulnerability of the GBM and a heterozygous variant was identified at c.4793 T > G (p.L1598R) in the COL4A3 gene. A previous report showed that a patient with c.4793 T > G in COL4A3 and c.448G > C in COL4A5 had irregular thinning of the GBM while his father with c.4793 T > G in COL4A3 did not show hematuria [ 14 ]. Another previous report analyzed 24 patients with autosomal recessive Alport syndrome, 17 of which had mutations in COL4A3 [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 17 patients, 13 had compound heterozygous mutations in COL4A3 , 5 of which had c.4793 T > G in COL4A3 . Among the parents of the 5 patients, only one mother with c.4793 T > G in COL4A3 had hematuria; the other parents seemed normal [ 14 ]. As the thinness of the GBM in the present case was not obvious and hematuria had not been pointed out previously, c.4793 T > G in COL4A3 might not have affected the synthesis of the triple helical molecule of the type IV collagen α3/4/5 chains.…”
Section: Discussionmentioning
confidence: 99%
“…In our community, previous studies reported Alport syndrome to be the most common cause of hematuria in Egyptian children and Alport syndrome represents > 16% of the original kidney disease in transplanted children [ 13 , 32 ]. Alport syndrome mostly presents with hematuria, but it may present with nephrotic syndrome even in the absence of hematuria [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%